PERCEPTION AND SATISFACTION AMONG OPEN AND DISTANCE LEARNING STUDENTS IN UNIVERSITI TEKNOLOGI MALAYSIA - Christnalter Bunsu; Noor Dayana Abd Halim (Інформаційні технології і засоби навчання, 2023)
In Universiti Teknologi Malaysia (UTM), the Open and Distance Learning (ODL) programme has been around quite recently and many things need to be discovered to improve it. The programme is running well and was already offered before the pandemic outbreak. However, a continuous evaluation is necessary to optimise both students’ learning and the quality of the education programme. The success of ODL programme could be affected by how it is viewed by the students involved in it and how satisfied they are with the overall learning experience. Therefore, this research was conducted quantitatively based on a survey research design, which aimed to identify students’ perception of and satisfaction with the ODL programme. The instrument used in this research is questionnaire with items adopted and modified from previous studies. Additionally, two educational technology lecturers with two-year experience in teaching the ODL programme were selected to validate the instrument. In this programme particularly, students were fully working adults with various backgrounds among them, ranging from local to international. A total of 107 students responded to the questionnaire and the data were analysed by using descriptive statistics. From the analysis, it was found that most students had a very positive perception and were highly satisfied with the ODL programme. It is hoped that the findings would be insightful for UTM, especially for the School of Education as a service provider, in taking professional consideration to improve the quality of the mentioned programme. Furthermore, these findings will provide useful insights for ODL lecturers in refining their teaching quality.